Secure Data Distribution using Secret Splitting over Cloud (Global Journal of Computer Science and Technology, 2017)
Developments are important to ride the unavoidable tide of progress. A large portion of undertakings are endeavoring to lessen their processing cost through the method of virtualization. This interest of diminishing the computing cost has induced the development of Cloud Computing. Cloud computing provides set of services to the customers over the network on rented basis which can be scaled up or down as per customers requirements. Typically cloud computing administrations are conveyed by an outsider supplier who possesses the foundation. In this paper we are focusing on secure data distribution over cloud using secret splitting. This will help us to achieve data confidentiality, integrity
Keywords: cloud computing; distributed computing; secret splitting; data confidentiality; integrity